2013
DOI: 10.1007/978-1-4614-7411-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection of Large Size to DCIS by Hypoxia and Angiogenesis Using NIRS

Abstract: This investigation aimed to test all tumor-bearing patients who undergo biopsy to see if angiogenesis and hypoxia can detect cancer. We used continuous-wave near-infrared spectroscopy (NIRS) to measure blood hemoglobin concentration to obtain blood volume or total hemoglobin [Hbtot] and oxygen saturation for the angiogenesis and hypoxic biomarkers. The contralateral breast was used as a reference to derive the difference from breast tumor as a difference in total hemoglobin Δ[HBtot] and a difference in deoxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Solid tumor growth generates multiple layers of cells that build a physical barrier to diffusion of oxygen, nutrients and metabolites (Vaupel and Harrison, 2004), leading to an hypoxic tumor microenvironment. This hypoxic microenvironment drives aggressive phenotype due to activation of various downstream signaling pathways (Nioka et al, 2013;Rankin and Giaccia, 2016;Singh et al, 2016;Vaapil et al, 2012). Hypoxic microenvironment further induces secretome containing sheddases and proteases that reshape the tumor microenvironment, modulate cellular phenotypes, and affect drug responses (Karagiannis et al, 2010;Miller et al, 2016;Miller et al, 2017;Rankin and Giaccia, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumor growth generates multiple layers of cells that build a physical barrier to diffusion of oxygen, nutrients and metabolites (Vaupel and Harrison, 2004), leading to an hypoxic tumor microenvironment. This hypoxic microenvironment drives aggressive phenotype due to activation of various downstream signaling pathways (Nioka et al, 2013;Rankin and Giaccia, 2016;Singh et al, 2016;Vaapil et al, 2012). Hypoxic microenvironment further induces secretome containing sheddases and proteases that reshape the tumor microenvironment, modulate cellular phenotypes, and affect drug responses (Karagiannis et al, 2010;Miller et al, 2016;Miller et al, 2017;Rankin and Giaccia, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, good image contrast was obtained, with promising prospects for early diagnosis and prescreening breast cancer. Nioka et al developed an approach based on NIR spectroscopy for breast tumor diagnosis in patients undergoing biopsy [30]. Continuous SW-NIR spectroscopy was employed to measure blood volume and blood hemoglobin concentration.…”
Section: Blood Oxygen Levelmentioning
confidence: 99%
“…It was concluded that smaller-size tumors are more challenging for detection by NIR spectroscopy, whereas ductal carcinoma in situ (DCIS) can be detected using configurations presented in the study. It was noted that for larger-size tumors, a significantly higher deoxygenation occurs in DCIS than in benign tumors [30].…”
Section: Blood Oxygen Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, diffuse optical imaging wherein individual microvessels are not spatially resolvable is also an emerging area of clinical optical imaging. [78][79][80][81][82][83][84][85] First described by Jöbsis in 1977, 86 near-infrared spectroscopy (NIRS) is the dominant diffuse optical imaging modality used in the clinic. NIRS uses near-infrared light (650-900 nm) and achieves deeper tissue penetration (e.g, mm to cm) than visible light at the expense of reduced spatial resolution.…”
Section: Op Tic Al Imag Ingmentioning
confidence: 99%